PENGENAAN TARIF RESIPROKAL OLEH AMERIKA SERIKAT TERHADAP KOMODITI INDONESIA: PELANGGARAN ASAS MOST-FAVOURED-NATION DANTARIFF BINDING: United States Reciprocal Tariffs Imposition on Indonesian Commodities: Violation of the Most-Favoured-Nation and Tariff Binding Principles - Nariman; Abrianti, Sharda (Faculty of Law, Universitas Trisakti, 2026)
The Most-Favoured-Nation and tariff binding principles state that when a WTO (World Trade Organization) member country implements a policy to reduce tariffs for its trading partners, it must extend the same treatment to all other trading partners. This requirement holds as long as the reduced tariffs do not exceed the negotiated tariff concessions. The United States imposed a 19% reciprocal tariff on all Indonesian commodities, both those covered and those not covered by the tariff concessions. The research question is whether the imposition of a 19% reciprocal tariff by the United States violates the Most-Favoured-Nation principle and tariff binding. The study approach used is normative legal research grounded in legal principles, using secondary data. The results of this study indicate that the United States has violated the Most-Favored-Nation and tariff binding principles by imposing a 19% reciprocal tariff on Indonesian commodities. This action creates unfavorable market access for Indonesian products in the United States compared to similar products from other WTO member countries. This conclusion that the United States’ actions could close market access for Indonesian commodities exported to the United States.